Chiang Mai: A Creative City Using Creative Tourism Management - Somnuxpong, Suprapa (Journal of Urban Culture Research, 2020)
This research article investigates how to use the physical, social, cultural and environmental potential of Chiang Mai province to increase the region’s cultural capital and develop more creative tourism management. The research showed that the diverse culture of Chiang Mai offers high potential for development of additional local community participation. Further local participation in creative tourism management can be supported by creating new tourism routes. This approach is consistent with the provincial policy on promoting the city’s creative economy and has received awards from The United Nations Educational, Scientific and Cultural Organization (UNESCO) for the Creative City (crafts and folk art).